(untitled) (Costos y Gestión, 2023)
In Argentina, the agricultural sector has had a prominent place in the national economy. With the objective of analysing the gross margin, this theoretical and empirical research developed using a non-experimental, descriptive and cross-sectional study design, has surveyed 67 soybean farmers from the agricultural dome of the Province of Chaco. The findings include the business model, the agronomic protocol and the gross margin as an indicator that allows comparing partial results -between activities, crops, technologies and campaigns- when considering the costs that are directly attributable to each cost unit. Although, in the agricultural sector, it is widely used due to its practicality, a point of the doctrine recognizes its limitations by excluding important components of the entity’s costs, and by erroneously establishing a causal relationship with the volume of activity which is based on considering as synonyms: direct and variable costs. This causality is appreciated through is the marginal contribution and it is important that the consultancy services provided to agricultural companies offer this alternative since, from the technical point of view, it is the one that allows explaining results related to management by linking costs and income in response to changes in the level of operation.